Prospects for Jamaica's political economy - Girvan, Norman P. (Friedrich Ebert Stiftung KingstonJM, 1986)
Retrospectively analyzes the last four years of the Manley period (1976-1980) and recent developments under Seaga's JLP. Suggests future strategies for Jamaica's political economy.